The management of indigenous problems. Formal indigenous organizations: purépecha nation, 1985-2005 (Tzintzun, Revista de Estudios Históricos, 2019)
The fundamental purpose of this work is to show the scenario, the factors and the circumstances that concurred around the configuration and performance of the formal indigenous groups in the state of Michoacán during the last third of the 20th century. With the case study of the so-called Purépecha Nation Organization (ONP), it is intended to demonstrate that the promoting social actors, mobilized outside the institutional instances, such as tenure headquarters and community property commissioners, to be assumed unilaterally and discretionary, as sedicent representatives of the Purépecha ethnic peoples. The ONP sought to strengthen and position itself with the generation of links and alliances with related groups of radical discursive tendencies, such as those that converged around the Zapatista National Liberation Army (EZLN) project. With this they proceeded to specify the direct interlocution with the three levels ofgovernment to demand the attention of its spectrum of disagreements, demands and expectations.